Green Islamic School: Integrating Environmental Education in the Islamic Education Curriculum - Juliani; Humam Mahdi; Shofy Widya Sari; Suci Indah Sari; Nadila Raihanun Nazwa (Yayasan Zia Salsabila, 2024)
This study aims to explore and analyze the efforts to integrate environmental education in the Islamic Religious Education (PAI) curriculum from an Islamic perspective. Environmental education in this context not only focuses on theoretical understanding of ecological issues, but also connects Islamic values related to nature and the environment, which are explained through verses of the Qur'an and hadith. This research uses a qualitative method with a case study approach to explore how environmental education is implemented in PAI learning, as well as to identify challenges and opportunities in its implementation. The results show that the integration of environmental education in the PAI curriculum not only shapes students' ecological awareness but also teaches the importance of maintaining the balance of nature as part of human responsibility as khalifah on earth. The program involves various practical activities, such as reforestation and waste management, which aim to instill Islamic values related to environmental conservation. Nonetheless, the study also noted some challenges, such as time and resource constraints, which need to be addressed to improve the effectiveness of this integration. Overall, this research makes an important contribution in understanding how Islamic religious education can play a role in creating broader environmental awareness among the younger generation.